The Cultural Origin of Saving Behavior - Joan Costa-Font; Paola Giuliano; Berkay Ozcan (Institute of Labor Economics (IZA), 2020)
Traditional economic interpretations have not been successful in explaining differences in saving rates across countries. One hypothesis is that savings respond to cultural specific social norms. A seminal paper in economics (1) however did not find any effect of culture on savings. We revisit this evidence using a novel dataset, which allows us to study the saving behavior of up to three generations of immigrants in the United Kingdom. Against the backdrop of existing evidence, we find that cultural preferences are an important explanation for cross-country differences in saving behavior, and their relevance persists up to three generations.
Keywords: Z1; D0; 330; saving; culture